Chest imaging cases - Bhalla, Sanjeev (New York : Oxford University Press, 2012)
'Chest Imaging Cases' thoroughly encompasses the field of thoracic radiology through 137 cases covering common and challenging radiologic and clinical issues.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chest -- Radiography -- Case studies; Diagnosis, Differential -- Case studies